Learning to "Think Like a Lawyer": Developing a Metacognitive Model for Legal Reasoning - Scott,Inara (College Teaching, 2021)
In the area of law, metacognition is an implicit goal of instruction, as legal studies classes often stress learning to “think like a lawyer.” However, the explicit metacognitive model for using legal reasoning to break down complex problems and seek solutions is rarely identified. This article explicitly identifies the metacognitive model for thinking like a lawyer and provides concrete steps for direct instruction in this method of analysis. The method of analysis and the resulting model are useful to beyond the legal studies classroom, as the legal reasoning model is substantially similar to a model for critical thinking.
Keywords: Business Law